Health regulation: demand and challenges of the family health strategy in an inland municipality of the State of Ceará, Brazil - Antonia Norma Teclane Marques; Renata de Sousa Alves; Luciana Macatrão Nogueira Nunes; Patrícia Freire de Vasconcelos; José Maria Ximenes Guimarães (Acta Scientiarum. Health Sciences, 2023)
This study aimed to analyze the demand profile and the challenges of regulating access to specialized care, considering the referenced cases and the perspectives of physicians in the Family Health Strategy (FHS). This was a mixed methods study, with a quantitative and qualitative approach, carried out in an inland municipality of the state of Ceará, Brazil. Quantitative data were obtained from Primary Health Care (PHC) referral forms, registered with the regulation center. Focus groups were held, involving 13 FHS physicians. The results showed 643 referrals, the majority (74.2%) corresponded to the request for tests, and 61.6% did not have a diagnostic hypothesis, which corroborates the increase in waiting time. Spine tomography was the exam with the highest amount in relation to the shortest waiting time. Regarding consultation, otorhinolaryngology was the specialty with the highest demand (17.7%). Physicians reported weaknesses and challenges in regulation, such as communication failures and the lack of counter-referral flows, which compromise Primary Health Care coordination, continuity and resolvability. The need to reorganize and qualify the regulatory processes in the municipality is pointed out.